Recognizing bio-literacy in nature: An ethnozoological photovoice-based approach to prospective teacher - Diana Hernawati; Vita Meylani (Institute of Advanced Engineering and Science, 2023)
This qualitative study aims to examine the learning experiences of prospective teachers through the photovoice approach. This research employs photovoice taken by the prospective teachers to obtain main themes regarding the scientific perceptions of the students in ethnozoological bio-literacy studies. This research was conducted in three different places, mountain sites, beaches, and nature reserve tourism destinations. There were 135 prospective teachers divided into nine groups producing 675 photos. The themes include several examples of animal rehabilitation for recovery, animal breeding and increasing of endemic animal populations to natural habitat (ex-situ), habituation of animals, changes in animal behavior, and sale of economically valuable animal shells. Study findings suggest that education must consider themes that arise in the surrounding environment to individualizing their observations in ways meaningful to them and enabling them to assimilate or accommodate the experiences to their schema. Drawing on this empirical evidence, the practical implication of ethnozoological photovoice is further discussed in this study. Based on the perspective of prospective teacher by the difference photograph and difference sites (mountain, beach, and nature reserve tourism) they are found the positive or negative meaning of photograph.